2013
DOI: 10.1016/j.jcmg.2012.10.023
|View full text |Cite
|
Sign up to set email alerts
|

Low-Dose Dual-Source CT Angiography With Iterative Reconstruction for Coronary Artery Stent Evaluation

Abstract: In selected patients, prospectively electrocardiography-triggered image acquisition with 80-kV tube voltage and low current in combination with IR permits the evaluation of patients with implanted coronary artery stents with reasonable diagnostic accuracy at very low radiation exposure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(36 citation statements)
references
References 22 publications
1
35
0
Order By: Relevance
“…This is of particular interest as a recent study demonstrated the feasibility of even low-dose CTA, however bearing limited evaluation capabilities regarding stents of less than 3 mm in diameter (13). In the current study, the stent diameter ranged from 2.25 to 4.0 mm.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…This is of particular interest as a recent study demonstrated the feasibility of even low-dose CTA, however bearing limited evaluation capabilities regarding stents of less than 3 mm in diameter (13). In the current study, the stent diameter ranged from 2.25 to 4.0 mm.…”
Section: Discussionmentioning
confidence: 85%
“…These advances were accompanied by reduced radiation exposure, eventually leading to lowdose coronary CTA with still acceptable image quality and sufficient predictive values even for the detection of in-stent stenosis (13).…”
Section: Introductionmentioning
confidence: 99%
“…Data from our study show that using conventional filtered back projection as the reconstruction method, an edge-enhancing kernel allows significantly less stent blooming and better image quality than a standard smooth kernel. Iterative reconstruction is a novel reconstruction method which reduces image noise [34] and can improve stent imaging [35][36][37]. Further studies could investigate the specific impact of iterative reconstruction on the effect of sharp versus smooth kernels in stent CT imaging.…”
Section: Discussionmentioning
confidence: 99%
“…Inclusion and exclusion criteria have been reported previously. 11 Stent-specific exclusion criteria were previous stent-in-stent placement, as well as stent implantation in bifurcation lesions. All patients gave written informed consent, and the study was approved by the institutional review board.…”
Section: Methodsmentioning
confidence: 99%